Oral origin of the placenta microbiome in pregnant women with preeclampsia - Cooper, Shontreal M.; Borgida, Adam; Thacker, Sejal; Hammer, Erica; Hariharan, Amirtha; Kuo, ChiaLing; Blanck, Nyle; Yuan, Hanshu; Panier, Hunter; Lin, Qingqi; Maas, Kendra; Campbell, Winston; et al. (Frontiers in Bacteriology, 2024)
Preeclampsia (PE) is a leading cause of morbidity and mortality in pregnancy with elusive etiology. Patients with PE are thought to be associated with higher rate of periodontal diseases (PD) and changes of oral bacteria with targeted PCR techniques. However, few studies have investigated associations between oral microbiome dysbiosis and secondarily disseminated microbes in the placenta simultaneously in patients with PE. It is also unclear the association between detected microbiome in placenta with systemic inflammation in PE. We enrolled 54 pregnant patients with and without PE and PD, and profiled the subgingival and placenta microbiome by V4 region of 16S rRNA gene sequencing. Systemic inflammatory markers tumor necrosis factor-alpha (TNF-α), C-reactive protein (CRP), lipopolysaccharide binding protein (LBP), interleukins 6 & 8 (IL-6, IL-8) in blood were measured by ELISA. We found that PD significantly increased the risk of PE after adjustments for age, and smoking status (OR=2.26, 95% CI=1.14-4.48, p=0.024). A combined group of oral associated bacteria Veilonella, Fusobacterium, Haemophilus, Granulicatella, Streptococcus, Gemella and Neisseria in placenta had significantly higher prevalence in women with PE compared to women without PE (53.8% vs 19.0%, p=0.018), with the highest prevalence in patients with both PE and PD (58.8%). The relative abundance of Haemophilus, Veillonella and Fusobacterium in subgingival samples was significantly higher in patient with PE than those without PE. The relative abundance of Haemophilus in subgingival samples was associated with increased risk of PE (OR=2.11, 95% CI=1.11-4.52, p=0.032). Proinflammatory cytokine analysis showed that PE patients with PD had higher blood IL-8 levels than PE patients without PD (p=0.